Shape files a data sheet for observed fluctuations of the Alerce glacier (1953-2020), North Patagonian Andes - Juan Cruz Ghilardi Truffa; Lucas Ruiz; Pierre Pitte; Lautaro Clavero (PANGAEA, 2024)
Glaciers in the northern Patagonian Andes show the highest rate of loss of all the Andean regions for the last decade. Detailed records of long-term variations in glacier extent are crucial to put current climate change into context and quantify its impact on mountain areas. In this study presents a detailed reconstruction of the extent (length and area) of the Alerce Glacier (41.15° S-71.81° W) over the past 70 years (1953-2020). Glacier fluctuations were mapped using historical documents, aerial photography and satellite images from US KH-9 Hexagon, Landsat and Pléiades. Four distinct methodologies were applied to measure glacier front positions: i) central flow line, ii) curvilinear box, iii) multiline, and iv) variable box. Each method was assessed for its ability to capture the magnitude of front position variations accurately.